IMPLEMENTASI PENDIDIKAN KARAKTER PADA SMP NEGERI KOTA PAREPARE - EFENDY, RUSTAN; M, AMIRUDDIN (P3M STAIN Parepare, 2014)
This study discusses about the implementation of character education in the town of Parepare. Samples were selected based on purposive sampling (samples intended). Type of research is a feld of research using qualitative descriptive analysis. The results showed that the implementation of character education at Secondary School Level town of Parepare is not maximized. The indicators include many still occur cheating in examinations, both at the level of indiscipline students and educators, and a lack of evaluation of the relevant parties. Therefore, repeninjauang important and more serious effort from both schools, teachers, pupils, parents, the wider community and the Department of Education for the City level with seriously address the issue of character education implementation and prepare facilities means that pre-associated with these efforts